Seismically induced racking of tunnel linings. - Penzien, Joseph (Earthquake engineering & structural dynamics.)
An analytical procedure is presented for evaluating the racking deformation of rectangular and circular tunnel linings caused by soil structure interaction during a seismic event. The procedure, as applied to rectangular linings, is supplementary to that previously published by Penzien and Wu for circular linings.